2013
DOI: 10.1021/bm400337f
|View full text |Cite
|
Sign up to set email alerts
|

Endosomolytic Reducible Polymeric Electrolytes for Cytosolic Protein Delivery

Abstract: Despite the numerous vital functions of proteins in the cytosolic compartment, less attention has been paid to the delivery of protein drugs to the cytosol than to the plasma membrane. To address this issue and effectively deliver charged proteins into the cytoplasm, we used endosomolytic, thiol-triggered degradable polyelectrolytes as carriers. The cationic, reducible polyelectrolyte RPC-bPEI0.8kDa2 was synthesized by the oxidative polymerization of thiolated branched polyethyleneimine (bPEI). The polymer was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 60 publications
1
23
0
Order By: Relevance
“…A previous report showed that the cationic polymers induce cytotoxicity by interacting with intracellular components and that higher molecular weight polymers have stronger interaction with these components, which results in higher toxicity. 42 The viability of the cells treated with either rPEI (16 kDa, 32 kDa) was above 76.8%, Characterization of Ad/Polymer Complex. The formation of Ad/polymers nanoparticles was driven by electrostatic interaction between Ad and rPEIs.…”
Section: ■ Results and Discussionmentioning
confidence: 96%
“…A previous report showed that the cationic polymers induce cytotoxicity by interacting with intracellular components and that higher molecular weight polymers have stronger interaction with these components, which results in higher toxicity. 42 The viability of the cells treated with either rPEI (16 kDa, 32 kDa) was above 76.8%, Characterization of Ad/Polymer Complex. The formation of Ad/polymers nanoparticles was driven by electrostatic interaction between Ad and rPEIs.…”
Section: ■ Results and Discussionmentioning
confidence: 96%
“…First, if acidic pH values can induce PheoA release from bPEI 25kDa ‐PheoA, then bPEI 25kDa ‐PheoA would need to be exposed to intracellular acidic environments such as those of late endosomes or lysosomes. However, the endosomal escape ability of bPEI 25kDa could prohibit the exposure of bPEI 25kDa ‐PheoA to these acidic compartments. Second, if bPEI 25kDa ‐PheoA enters the cell through direct membrane penetration (given that polycations such as bPEI can penetrate through the plasma membrane and detour from endocytic pathways), bPEI 25kDa ‐PheoA would be located in the cytosol after cellular internalization.…”
Section: Resultsmentioning
confidence: 99%
“…Various methods of thiolation have been reported (Figure ). Among the most common are methods that use reaction of iminothiolane with primary amines of a polycation such as PEI and poly( L ‐lysine) (PLL) . Using iminothiolane conserves the number of positive charges of the polycation and is applicable to both conventional synthesis of polycations as well as in situ formation of bioreducible polycations after polyplex formation with thiolated polycations.…”
Section: Synthesis Of Bioreducible Polycationsmentioning
confidence: 99%